Assessment of the objective conditions of scientific research activity in Russia - V. E. Statsenko (Вестник Северо-Кавказского федерального университета)
In the Russian Federation, scientific research and development are the basis of innovative and investment development of the country. In this regard, the article analyzes the dynamics of indicators of research activity in Russia from 2010 to 2021. Analytical data on the number of organizations implementing research processes and engaged in experimental design developments, qualitative and quantitative characteristics of personnel involved in scientific activities, as well as features of financing research work, allowing to identify problem areas of dynamic development of innovative processes in the country. Within the framework of the study, a quantitative empirical study was organized and performed based on the use of economic and statistical tools: comparison, dynamic series method, index method, graphical modeling, etc. The choice of specific techniques and methods is due to the real interrelation of the phenomena and processes under consideration. The study is based on the analysis of statistical data presented in Russian statistical yearbooks. As a part of the study of national innovation processes in 2010–2021, an increase in the number of organizations performing research and development in various areas of the economy was noted. The results of the analysis revealed a positive trend of state support for young scientists and researchers in the country. However, insufficient effectiveness of the state policy in the field of scientific potential formation at the level of universities, academies and institutes was noted. An assessment of the structure of R&D financing in the Russian Federation indicates that the main source of investment is the state budget and annually accounts for more than 60% of the total cost. At the same time, the statistical data clearly reflected the deterioration of the investment climate under the sanctions of 2020–2021. The results of the study revealed a significant fluctuation in the indicators of research and development activities in the Russian Federation in 2010–2021. At the same time, it was noted that there are prerequisites for ensuring positive dynamics of national innovation processes.